Rancang Bangun Website Sekolah Pintar Menggunakan Laravel Dengan Chatbot Informasi Akademik Otomatis - Dian Wahyu Pratama; Ahmad Chamsudin (STIKOM Tunas Bangsa Pematangsiantar, 2026)
Limited access to fast and well-structured academic information remains a challenge at the elementary school level, including at SDN 4 Karangrayung. The conventional method of information delivery has resulted in less effective communication between the school and parents. This study aims to develop a web-based Smart School website integrated with an automatic academic information chatbot as a digital information service platform. System development uses the Research and Development (R&D) method with the Waterfall model, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The website was built using the Laravel framework with MySQL database support, while the chatbot was designed using a rule-based approach to provide automated responses to user inquiries. The system features include school profiles, teacher data, news and activities, gallery, contact information, and an online academic question-and-answer service accessible to students and parents. Black-box testing results showed a 100% success rate, while the media feasibility evaluation achieved a score of 86%, categorized as “Very Feasible.” The implementation of this system enhances the effectiveness of information dissemination and supports digital transformation in elementary education.